2021
DOI: 10.1097/mcp.0000000000000823
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 outcomes in people with cystic fibrosis

Abstract: Purpose of reviewThe COVID-19 global pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has had a dramatic impact that is still ongoing around the world. Cystic fibrosis (CF) has been identified as a possible risk factor of poor outcome.Recent findingsData collected by multiple National CF registries around the world have indicated that persons with CF (PwCF) are not more likely to be affected by SARS-CoV-2 than the general population. The course of SARS-CoV-2 is usually mild i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 51 publications
0
17
0
1
Order By: Relevance
“…The impact of SARS-CoV-2 infection in patients with cystic fibrosis (CF) was lower than expected, 104 , 105 , 106 , 107 but older patients, those with lower lung function, CF-related diabetes and those who received a solid organ transplant 108 , 109 , 110 experienced a more unfavorable evolution.…”
Section: Cystic Fibrosismentioning
confidence: 93%
See 1 more Smart Citation
“…The impact of SARS-CoV-2 infection in patients with cystic fibrosis (CF) was lower than expected, 104 , 105 , 106 , 107 but older patients, those with lower lung function, CF-related diabetes and those who received a solid organ transplant 108 , 109 , 110 experienced a more unfavorable evolution.…”
Section: Cystic Fibrosismentioning
confidence: 93%
“…Procedures such as respiratory function tests have been drastically reduced and remote attention such as telehealth, 120 , 121 , 122 , 123 home spirometry, 108 home collection of sputum samples, 124 home delivery of medication from the hospital pharmacy, and long-distance electronic monitoring 123 were required. This provided an opportunity to take new approaches to improving CF patients care with new and effective models, with durable changes in the future CF health care ( Fig.…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…Cystic fibrosis (CF) and myasthenia gravis (MG) are two such comorbidities. While outside of pregnancy, most patients with CF (homozygous for the cystic fibrosis transmembrane conductance regulator (CFTR) gene) and COVID-19 are young and can have a mild course, they tend to show higher rates of severe outcomes, mostly due to low lung function and/or a history of transplantation [ 4 ]. While COVID-19 may worsen the outcome in non-pregnant patients with MG, a recent systematic review could not definitively establish causation of increased morbidity [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Any supplementary respiratory condition can have a severe course in these patients given the chronic microbial lung colonization or infection and the constant deterioration in functioning of the lungs [ 11 ]. However, the course of COVID-19 disease in patients with CF appears to be favorable [ 1 , 2 , 12 ]. Nevertheless, recent studies have shown that lung and pancreatic impairment are risk factors for severe COVID-19 in these patients [ 4 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the course of COVID-19 disease in patients with CF appears to be favorable [ 1 , 2 , 12 ]. Nevertheless, recent studies have shown that lung and pancreatic impairment are risk factors for severe COVID-19 in these patients [ 4 , 12 ]. Therefore, any CF patient with SARS-CoV-2 infection requires a comprehensive evaluation, taking into account all associated comorbidities, in order to tailor a personalized management plan.…”
Section: Discussionmentioning
confidence: 99%